Optimasi Pendidikan Inklusif: Meningkatkan Keterampilan dan Pengetahuan Guru di SD Muhammadiyah 1 Candi - Arti, Widi; Wati, Tri Linggo; Widanti, Herista Novia; Hanum, Sri Mukhodim Faridah; Fannysah Zahwa, Faradiva; Gilang Putri, Ardilia (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: SD Muhammadiyah 1 Candi is an inclusive school that has been established for the last five years. The school implements inclusive education for diverse types of learners. However, challenges arise when most teachers have only a general education background and lack understanding of the needs of children with special needs. This service aims to improve teacher skills in implementing learning through special visual media for children with special needs. And also aims to increase teachers' understanding of reproductive health and mentoring students in the early puberty period. Method: The partner of this activity is SD Muhammadiyah 1 Candi. The first workshop related to reproductive health was attended by 27 fourth, fifth, and sixth grade teachers. The learning method used is Problem Based Learning, where all participants are actively involved. The second workshop on the use of visual media in learning was attended by 25 participants, including regular teachers and accompanying teachers, for grades one, two, and three. Results: 1) Increased Teacher Knowledge about Reproductive Health and Student Assistance in Early Puberty: The workshop succeeded in increasing teacher knowledge about reproductive health and mentoring students in early puberty; 2) Improving Teacher Skills in Utilizing Visual Media: The workshop with a Problem Based Learning approach succeeded in improving teachers' skills in using special visual media for children with special needs (ABK). Conclusion: The workshop with the Problem Based Learning method succeeded in improving teacher skills in utilizing visual media and reproductive health education for teachers.